The Influence of Perception of Ease and Perceived Usefulness on Interest in Using E-Money in FE UNJ Students Through Trust as a Mediation Variable - Maharani, Fauziah; Usman, Osly (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This study aims to determine the influence of perception of ease and perceived usefulness on interest in using E-Money in FE UNJ students through trust as a mediation variable. This study used quantitative methods by using questionnaires as a way of data collection. The population in this study is FE UNJ students who are still active as students and use E-Money totaling 998 people. Determination of the sample using the slovin formula so that the sample used amounted to 285 students. The technique used for sampling uses purposive sampling. The measurement scale uses a Likert scale of 1-5. Data analysis techniques use PLS analysis which consists of measurement model analysis, structural models, and hypothesis testing using SmartPLS 4.0. Based on the results of the study, the results show that the perception of ease, perceived usefulness, and trust has a positive and significant effect on the interest in using E-Money, the perception of ease and perceived usefulness has a positive and significant effect on trust, trust has a positive and significant effect on the interest in using E-Money, trust is able to mediate positively the influence of perceived usefulness but unable to mediate the influence of perception of ease on interest in using E-Money. This discovery implies that interest in using E-Money is influenced by several factors. For E-Money service providers, this research can provide promotions regarding the ease and benefits provided by E-Money to students so as to expand the market and increase trust by ensuring security when making transactions, and providing good service.